Assessment of symptoms of temporomandibular dysfunction in patients undergoing orthodontic treatment using occlusal lift - Isabella Avelar Santos; Gracia Lopes Costa; Rodrigo Bernardes Pereira; Thiago Bezerra Leite; António Sérgio Guimarães; Luciane Lacerda Franco Rocha Rodrigues (BrJP)
BACKGROUND AND OBJECTIVES: The use of orthodontic appliances is constantly associated with symptoms of temporomandibular disorder (TMD). In this sense, the present study aimed to investigate the development of TMD symptoms in patients undergoing orthodontic treatment with occlusal lifting. METHODS: This is a longitudinal, quantitative and descriptive study; 40 patients with an indication for orthodontic treatment, participating in the study. They were evaluated: before the start of orthodontic treatment (T0), 24 hours (T1) and 30 days (T2) after installation of the occlusal elevator. Symptom assessment was carried out by applying the DC/TMD symptom questionnaire. The assessment of psychosocial factors was carried out using the “WISE Clinicians” test (Web Based Interdisciplinary Symptom Evaluation). The data were entered into a Microsoft Excel spreadsheet for statistical analysis using the Chi-Square test, with a significance level of 5%. RESULTS: In the T1 assessment, 42.50% (n= 17) of patients reported feeling any type of pain and 57.50% (n= 23) did not feel any pain. At T2, the proportion of patients who reported pain was 30% (n= 12), while 70% (n= 28) did not show any symptoms; 10% (n=10) of patients reported pain at both times; 37.50% (n=15) did not experience pain at any time during the assessment; 32.50% (n=13) assessed pain at the first moment and after the second assessment they no longer expressed pain. CONCLUSION: It can be concluded that occlusal lifting was not significant in terms of pain in most patients and when compared to the control group.